2022
DOI: 10.15406/jbmoa.2022.10.00329
|View full text |Cite
|
Sign up to set email alerts
|

Novel transdermal patch for detecting Cystic fibrosis

Abstract: A genetic condition, termed as cystic fibrosis (CF) affecting numerous organs, including the lungs, pancreas, colon, liver, and reproductive system, is completely dormant and intrinsic. Better treatment and control of CF are facilitated by early diagnosis. With the advent of technological and healthcare developments, there have been tremendous advancements in detecting CF rapidly and administering therapeutics. Accordingly, these short communication overviews developments related to early diagnosis of CF with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Similarly, Biswas et al reported a novel transdermal patch for cystic fibrosis diagnosis. 120 The patch, which looks like a conventional sticker, absorbs sweat through tiny canals. Pilocarpine, a drug that stimulates sweat production, is applied to the skin using a mild electric current.…”
Section: Biofluidsmentioning
confidence: 99%
“…Similarly, Biswas et al reported a novel transdermal patch for cystic fibrosis diagnosis. 120 The patch, which looks like a conventional sticker, absorbs sweat through tiny canals. Pilocarpine, a drug that stimulates sweat production, is applied to the skin using a mild electric current.…”
Section: Biofluidsmentioning
confidence: 99%